H3K36 Methylation in Neural Development and Associated Diseases - Zaghi, Mattia; Broccoli, Vania; Sessa, Alessandro (Frontiers in Genetics, 2020)
Post-translational methylation of H3 lysine 36 (H3K36) creates important epigenetic marks that heavily contribute to the functionality of the chromatin. These marks are interpreted by the cell in several crucial biological processes including gene transcription and DNA methylation. Thus, the homeostasis of H3K36 marks is finely regulated by different classes of enzymes that, whether impaired leads to a plethora of diseases spanning from multi-organ syndromes to cancer, to pure neurological diseases often associated with brain development. This mini-review summarizes current knowledge on these important epigenetic signals with emphasis on the molecular mechanisms that (i) regulate their abundance, (ii) be influenced by H3K36 methylation and on (iii) the associated diseases.